Separation of Xylose From Glucose Using Thin Film Composite (TFC) Nanofiltration Membrane: Effect of Pressure, Total Sugar Concentration and Xylose/Glucose Ratio - K. H., Mah; Wan Mohd Hafizuddin, Wan Yussof; Mazrul Nizam, Abu Seman; N., Zainol (Penerbit Universiti Teknologi Malaysia, 2014)
Xylose is an abundant raw material coexists with other sugars that can be turned into useful products, such as ethanol, xylitol and 2, 3-butanediol by microorganism such as yeasts, bacteria, and mycelial fungi. However, more than 80 % of the production cost of these products comes solely from the production of xylose. Presently, the separation of xylose from hemicellulose hydrolysate relies on chromatographic separation alone. The use of nanofiltration membrane may offer alternative in recovering xylose due to the differences in size compared to other sugars. The aim of this study is to evaluate the ability of membrane developed by interfacial polymerization reaction between triethanolamine (TEOA) (6 % w/v) and tri-mesoyl chloride (TMC) (0.15 % w/v) as monomers on polyethersulfone (PES) microporous substrate to separate xylose from glucose. In this study, factors affecting the process, namely pressure, concentration of total sugars in solution, and composition of monosaccharides in total sugar, were investigated using two-level factorial analysis. The experiment was performed using Amicon Milipore stirred cell (Model 8200) with constant stirring speed at 300 rpm and temperature at ambient. The glucose and xylose concentration was quantified using high performance liquid chromatography (HPLC). It is found that the developed nanofiltration membrane has the ability to separate xylose from glucose.The analysis of the experimental response revealed that the total sugar concentration and composition ratio of xylose: glucose had significant interactive effect on xylose separation factor. Overall from the present study, it can be concluded that nanofiltration has high potential to replace currently in use chromatographic method in xylose separation.